KEADILAN BAGI KORBAN: KAJIAN VIKTIMOLOGI DALAM PENANGANAN KASUS TRAGEDI KANJURUHAN - Syahnan Habibi Nasution; Ahmad Deedad (Pengelola Jurnal Politeknik Negeri Ketapang, 2026)
The Kanjuruhan Tragedy is one of the most devastating humanitarian incidents in the history of Indonesian football, resulting in significant loss of life and numerous injuries. This event not only caused physical harm but also deep psychological trauma for the victims and their families. This study aims to analyze how justice for victims is understood and implemented through a victimological perspective in handling the Kanjuruhan Tragedy case. The research employs a normative juridical method with statutory and conceptual approaches. The findings indicate that the handling of this case still faces various challenges, particularly in fulfilling victims’ rights such as restitution, rehabilitation, and guarantees of non-repetition. A victimological perspective emphasizes the importance of placing victims at the center of the justice process (victim-centered justice), focusing not only on punishing perpetrators but also on the comprehensive recovery of victims. Therefore, more comprehensive efforts are required from the state and law enforcement authorities to ensure substantive justice for victims, including through policy reforms and more effective victim protection mechanisms.